Psychological Profile of Children with Headache and Recurrent Abdominal Pain - J Gordon Millichap (Pediatric Neurology Briefs, 2007)
The psychological profile of 70 patients (age range 4-18 years; mean 11 years) with headache, 70 with recurrent abdominal pain (RAP), and 70 controls was compared using the Child Behaviour Checklist 4-18 (CBCL).